PENERAPAN AR DALAM MEDIA PEMBELAJARAN KLASIFIKASI BAKTERI - Moch. Aditya Febriza; Qadhli Jafar Adrian; Adi sucipto (Department of Biology Education, Faculty of Education and Teacher Training, UIN Sunan Gunung Djati Bandung, 2021)
Bacteria is an important science to study. In the world of education itself, the material that discusses bacteria is contained in the 2013 Revised Curriculum, the material for class X (ten) in the second semester, High School in the Mathematics and Natural Sciences Specialization Group. In studying bacteria in schools still using conventional methods, and still minimal use of technology, by utilizing AR technology the aim of this research is to create a learning process that is more interesting and easier. The process of making learning media for AR Classification of Bacteria uses the Multimedia Development Life Cycle (MDLC) system development method. In this study, the stages in the testing carried out included testing the aspects of learning design based on the aspects and assessment criteria of learning media which got a percentage of 98.75%, which means that the material contained in this application is very good, then for testing the functionality, the results show that this application 100% can run according to the design that has been made without problems, then for testing ISO 25010 on the Operability Aspect, a value of 88% is obtained or it means very good, so that the learning media for the AR Classification of Bacteria have been considered very good and interesting to use and easy to use.     Abstrak. Bakteri menjadi materi yang membahas tentang mikroorganisme yang tertuang di Kurikulum 2013 Revisi, materi di kelas X (sepuluh) semester ke dua, Sekolah Menengah Atas di Kelompok Peminatan Matematika dan Ilmu Pengetahuan Alam. Dalam mempelajari bakteri di Sekolah umumnya masih menggunakan metode konvensional, dan masih minim pemanfaatan teknologi, dengan memanfaatkan teknologi AR tujuan dalam penelitian ini adalah untuk menciptakan proses pembelajaran yang lebih menarik dan lebih mudah. Proses pembuatan media pembelajaran AR Klasifikasi Bakteri menggunakan metode pengembangan sistem Multimedia Development Life Cycle (MDLC). Dalam penelitian ini tahapan dalam pengujian yang dilakukan meliputi pengujian aspek desain pembelajaran berdasarkan aspek dan kriteria penilaian media pembelajaran yang mendapatkan hasil persentase sebesar 98,75% yang berarti materi yang terdapat dalam aplikasi ini sudah sangat baik, kemudian untuk pengujian fungsionalitas didapatkan hasil bahwa aplikasi ini 100% dapat berjalan sesuai dengan rancangan yang telah dibuat tanpa kendala, kemudian untuk pengujian ISO 25010 pada Aspek Operability didapatkan nilai sebesar 88% atau berarti sangat baik, sehingga media pembelajaran AR Klasifikasi Bakteri ini sudah dinilai sangat baik serta menarik untuk digunakan dan mudah untuk diimplementasikan.